Determinan Keikutsertaan Wanita Usia Subur dalam Pemeriksaan IVA di Kabupaten Poso - Lisda Widianti Longgupa (Jurnal Bidan Cerdas, 2019)
Cervical cancer is a preventable disease, but in fact, women are often found at advanced disease because they do not undergo screening. The purpose of this study was to analyze the relationship between socio-demographic factors, cost, knowledge, and attitude with women’s participation in VIA test. The design of this study was cross-sectional. The samples were taken from women who received counseling about cervical cancer during 2016 at districts Health Center by using proportional random sampling. Overall respondents were 198 women. The data were processed and analyzed by using Chi-Square, eta correlation, phi correlation, and multiple logistic regression. Bivariable analysis showed that age (p-value <0.001), education (p-value <0.001), employment (p-value = 0.008), income (p-value = 0.036), marital status (p-value = 0.010), distance (p-value = 0.008), cost (p-value <0.001, knowledge (p-value <0.001), and attitude (p <0.001) were significantly related with women’s participation in VIA test. Multivariable analysis showed that marital status, knowledge and attitude were significantly related with women’s participation in VIA test. Attitude was variable with the largest value of prevalence rate, it was 20,4 and p value<0,001. The conclusions that can be taken in this study includes socio-demographic factors were associated with women’s participation in VIA test, except parity; the cost has weak relationship with women's participation in VIA test; knowledge has fairly strong relationship with women's participation in VIA test; attitude has fairly strong relationship with women's participation in VIA test and attitude is the most dominant factor related with women's participation in VIA test